Лингострановедческая направленность уроков английского языка в обучении детей с особыми образовательными потребностями [Articol] - Zorilo, Larisa; Adamco, Tatiana (USARB, 2018)
This article deals with the problem of the lingo-cultural orientation of the English language lessons in teaching children with special educational needs. The features of teaching a foreign language to children with special educational needs, organizational and methodological aspects of this teacher's work in an inclusive class are shown in this work. The author gives the examples of the teacher's work during extracurricular activity, and justifies the used methods.
Keywords: children with special educational needs; lingo-cultural orientation of studying a foreign language; extra-curricular work